N‐Heterocyclic Carbene Ligand‐Enabled C(sp3)−H Arylation of Piperidine and Tetrahydropyran Derivatives. Issue 14 (24th February 2016) - Ye, Shengqing; Yang, Weibo; Coon, Timothy; Fanning, Dewey; Neubert, Tim; Stamos, Dean; Yu, Jin‐Quan
Abstract: Pd II ‐catalyzed C(sp 3 )−H arylation of saturated heterocycles with a wide range of aryl iodides is enabled by an N‐heterocyclic carbene (NHC) ligand. A C(sp 3 )−H insertion step by the Pd II /NHC complex in the absence of ArI is demonstrated experimentally for the first time. Experimental data suggests that the previously established NHC‐mediated Pd 0 /Pd II catalytic manifold does not operate in this reaction. This transformation provides a new approach for diversifying pharmaceutically relevant piperidine and tetrahydropyran ring systems. Abstract : Pd II ‐catalyzed C(sp 3 )−H arylation of saturated heterocycles with a wide range of aryl iodides is enabled by an N‐heterocyclic carbene (NHC) ligand. A C−H insertion step by the Pd II /NHC complex in the absence of ArI is demonstrated experimentally for the first time. This arylation method provides a new approach for diversifying pharmaceutically relevant piperidine and tetrahydropyran ring systems (see scheme).